"India's Rasputin"?: V.K. Krishna Menon and Anglo–American misperceptions of Indian foreign policymaking, 1947–1964 - McGarr, Paul M. (Taylor & Francis (Routledge), 2011)
From 1947 until his political demise in late 1962, Vengalil Krishanan Krishna Menon stood at the forefront of India's international relations. One of Indian Premier Jawaharlal Nehru's closest political confidantes, Menon served variously as India's High Commissioner to the United Kingdom, leader of its delegation to the United Nations, self-styled mediator in the Korea, Indo–China, and Suez crises of the 1950s and, from 1957, his country's Defence Minister. Vilified in the West as “India's Rasputin,” Menon's left-wing credentials, anti-colonial rhetoric, and willingness to engage with the Communist bloc were seen by Anglo–American diplomats as a threat to Western interests in South Asia. Drawing upon recently released British and American archival records, this article argues that Western misperceptions of Menon, and his role in the Indian foreign policy-making process, undermined Anglo–American relations with India for much of the early Cold War.